KAJIAN SISTEM BUKAAN KAMAR TIDUR ASRAMA BEIYUAN GXNU TERHADAP KENYAMANAN TERMAL DAN PENCAHAYAAN ALAMI RUANG - CITRA AMELIA (Serat Rupa: Journal of Design, 2016)
Dormitory played an important role on university students life. Lot of universities oblige their students to live inside universityâ€™s dormitory with consideration that that thing would make observing students activities easier. Dormitory bedrooms comfort were crucial. This because of bedroom was the place where students would comeback to get a good rest after their daily activities outside. One of many things that could determine one rooms comfort was apertures design. Apertures design would affect a room wind circulation. Aside from natural circulation, apertures would determine the intensity of natural lighting that can get into the room. Â Keywords: climate; lighting; students activity; temperature